2020
DOI: 10.1016/s2215-0366(20)30421-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between mental illness and COVID-19 susceptibility and clinical outcomes in South Korea: a nationwide cohort study

Abstract: Background Evidence for the associations between mental illness and the likelihood of a positive severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) test result and the clinical outcomes of COVID-19 is scarce. We aimed to investigate these associations with data from a national register in South Korea. Methods A nationwide cohort study with propensity score matching was done in South Korea using data collected from the Health Insurance Review and Assessment Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
236
3
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 225 publications
(266 citation statements)
references
References 29 publications
5
236
3
10
Order By: Relevance
“… 14 Nevertheless, we interpret this finding cautiously, as a Korean study found no association between psychiatric diagnosis and COVID-19 diagnosis, albeit in a much smaller sample and with less matching. 15 Possible explanations for the association include behavioural factors (eg, less adherence to social distancing recommendations) and residual socioeconomic and lifestyle factors (eg, smoking) that are not sufficiently captured by the available data in any of the studies. It could also be that vulnerability to COVID-19 is increased by the pro-inflammatory state postulated to occur in some forms of psychiatric disorder or be related to psychotropic medication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 Nevertheless, we interpret this finding cautiously, as a Korean study found no association between psychiatric diagnosis and COVID-19 diagnosis, albeit in a much smaller sample and with less matching. 15 Possible explanations for the association include behavioural factors (eg, less adherence to social distancing recommendations) and residual socioeconomic and lifestyle factors (eg, smoking) that are not sufficiently captured by the available data in any of the studies. It could also be that vulnerability to COVID-19 is increased by the pro-inflammatory state postulated to occur in some forms of psychiatric disorder or be related to psychotropic medication.…”
Section: Discussionmentioning
confidence: 99%
“… 14 However, a Korean study found no such associations, except for patients with schizophrenia. 15 Reliable estimation of a possible increased risk of COVID-19 among patients with psychiatric illness requires large, well-controlled cohort studies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the increased risk that pre-existing physical health conditions create for COVID-19 and related outcomes, emerging evidence shows that pre-existing mental health conditions may also confer significant risk for infection as well as increasing risk for hospitalization and mortality among positive screens ( Wang et al., 2020 ; Brown et al., 2020 ), however findings remain mixed. For example, initial evidence from South Korea examined the risk of COVID-19 infection and severity of outcomes across a nationwide cohort and found that pre-existing mental health conditions did not significantly increase risk for infection and there was a marginal increased risk for severe outcomes ( Lee et al., 2020 ). Conversely, evidence that became available as of November 2020 is demonstrating that individuals with pre-existing and recently diagnosed mental health conditions have a higher risk of infection, higher risk of hospitalization after infection, and an increased risk of mortality compared to individuals without diagnosed mental health conditions ( Wang et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among possible options, psychotropic drugs have been considered as possible prevention strategies. Indeed, given the numerous factors which might increase the risk of having a severe COVID in patients with psychiatric disorders, it is surprising that the initial prevalence of COVID, during the first wave and based on the first-published reports, was apparently similar or only slightly higher in patients with mental illness compared to the general population [ 1 , 2 ]. As some authors have recently suggested, this could be indicative of a prophylactic effect against SARS-CoV-2 shared by psychoactive agents commonly used to treat psychiatric patients [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%